Research of the Contact Voltages Distribution on the Front and Back Surfaces of the Cutter - Urinov Nasillo Faizilloevich; Ramazonov Azizbek Chori ugli (Zien Journals, 2022)
The methods for measuring contact stresses (loads) on the working surfaces of the tool are covered and analyzed in the article
Keywords: model; polarization-optical method; interference method; cutter